Polski ruch pozytywnej seksualności a teoria queer. Studium przypadku - Lisowska, Katarzyna (2022)
The aim of the paper is to discuss Polish sex positivity movement and its relationship to queer theory. This is done on the basis of a case study, i.e. the analysis of the book Warsztaty intymności [The workshops of intimacy] by Agnieszka Szeżyńska. The author of the article presents selected aspects of this publication, focusing on the typical features of sex positivity approach (in so doing, she refers to other Polish and English sources which represent or study this topic). Apart from that, the scholar shows conceptual overlaps between Szeżyńska’s perspective and queer theory. In conclusion, the author discusses the functioning and possible outcomes of this alliance in the Polish context.
Keywords: sex positivity; queer theory; feminism; gender; sexuality; consent; pleasure